E-Commerce Pada Perusahaan Cv. Bulu Nusantara Gresik (Studi Kasus : Program Studi Teknik Informatika Universitas Wijaya Kusuma Surabaya) - Muhammad Syamsuddin; Emmy Wahyuningtyas (Melek IT : Information Technology Journal, 2019)
The results of abundant and qualified animal feed raw materials is one of the signs that a company has successfully become a company worthy to be trusted by the public. To get a large number of consumers requires a great effort and large funds as well. In getting the consumer needs a promotion which can attract potential buyers to buy raw materials for animal feed, in the company CV. Fur Nusantara gresik still constrained in the process of marketing its products are still from mouth to mouth. This study uses e-commerce method that has research steps are: Observation, Library Studies, Primary and Secondary. The results of this study can perform the promotion of Livestock Feed Raw Materials in the company CV. Bulu Nusantara Gresik, report the price data of Livestock Feed Raw Materials and sample sempel images of each raw material in the form of e-commerce.